Bimbingan kelompok dengan teknik self management untuk mengurangi kecemasan komunikasi interpersonal pada aspek kognitif siswa - Dian Mayasari; Iip Istirahayu (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
Students as social beings should be able to do with good interpersonal communication. The fact that not all students can communicate with good interpersonal communication because of their apprehension. This study aims to analyze decreased students interpersonal communication apprehension on the cognitive aspects in state 21 Junior High School Pontianak. The method used in this study was the quantitative. This study population were students of class VII F state 21 junior high school pontianak amounting to 41 students and sampling techniques by purposive sampling with a total of 10 students. The results of this study indicate that there is a decline in interpersonal communication apprehension on cognitive aspects by 9.5 points or by 19.79% after being given of group counseling with self-management techniques.